PELATIHAN PEMBUATAN HANDY CRAFT UNTUK GURU-GURU SLTP DI DAERAH ISTIMEWA YOGYAKARTA - Zuni K, Enny; Yuh Suprihatin, Emy; Bariqina, Endang (Universitas Negeri Yogyakarta, 2003)
This Community Service Program is intended to (1) provide knowledge and skills on local content subject-matter PKK for Junior High School teachers, such as handycraft which is made from natural materials, textile, and recycled materials, (2) develop the PKK teachers' creativity in handycraft making for Junior High School students.This training uses classical approach for teoritical material and individualapproach for practical material. In oeder to get optimal results, an intimate individual guidance is provided during the practical process. Evaluation is performed during the practical process, practical outcomes, and post-training periods.Outcomes of this training are handicraft products such as: (l) picture framefrom cardboard covered with dried leaves, (2) mascot from batik's scraps, (3) buffetdecoration from bathing soap and water lace, (4) pencil cap from flannel, and (5) free style works, such as accessories from banana stem and tissue box from used ice cream spoon. Results of the evaluation on the participants' works show that 42 % of the participants' reach the excelent category. The observation performed after the training show that 90% of the participans have implemented the training outcomes.the material most frequently implemented for the junior high school sudents in the making of picture frame from cardboard and dried leaves, where as the least frequent materials implemented is book self decoration form bathing soap and water lace. This is due to the relatively high price of the material and need more difficult material preparation than the others. The participants' responses during the training are very good, these are proved by their enthusiasm and determination in performing tasks given by their respective instructor as well as the participants' comments about their impression and messages indicating that this training can open the insight and blow fresh wind for the local content subject-matter PKK. Key words: handicraft.